Antioxidant and Antibacterial Effects of Some Medicinal Plants of Iran - Samira Mohammadi; Khosro Piri; Mehri Dinarvand (International Journal of Secondary Metabolite)
Medicinal plants used in the treatment of diseases earlier times are potential sources of new drugs. The present study was undertaken to study the chemical composition, antioxidant and antibacterial activity of certain medicinal plants of Iran by gas chromatography and mass spectrometry (GC/MS), DPPH and disk diffusion method. According to the results of GC/MS, there are 46 kinds of chemical compounds including mucilage, fatty acids, flavonoid and diterpenes in flower of Echium khuzistanicum. There are aldehydes (7.9%), phenols (7.5%), fatty acids (5.8%) and furfural (5.4%) in the methanol extract of Echinops cephalotes. Furfural, steroids, vitamin B and flavonoids are the main compounds of Marrubium anisodan. Results of the antibacterial test showed that Staphylococcus aureus and Bacillus subtilis were more sensitive to methanol extract of Echium khuzistanicum root. Pseudomonas auruginosa was more sensitive to DMSO extract of Marrubium anisodan at 600 mg/ml concentration. Maximum flavonoid and phenol contents were belonging to Echinops cephalotes. Marrubium anisodan showed the best DPPH free radical scavenging activity.